181k views
4 votes
F(x)=6x^2-x
Find f(-3)

2 Answers

6 votes

Answer:

327

Explanation:

You will plug in the -3 for x. 6 times -3 equals -18. -18 squared equals 324. 324 minus -3 equals 327.

User Oussama Boussif
by
5.4k points
7 votes

Answer:
f(-3)=57

Explanation:

Given the following function:


f(x)=6x^2-x

To find
f(-3) you need to substitute the x value
x=-3 into the function
f(x) given.

Therefore, when the input value (value of the variable "x") is -3, then the ouput value is:


x=-3\\\\f(-3)=6(-3)^2-(-3)

Remember the multplication of signs:


(+)(+)=+\\(-)(-)=+\\(-)(+)=-

Then:


f(-3)=57

User Changtung
by
6.2k points